Timely referral to health centers for the prevention of cardiovascular diseases: IraPEN national program - Hadavandsiri, Fatemeh; Khalili, Davood; Mahdavi, Alireza; Afkar, Mehdi; Ostovar, Afshin; Hashemi-Nazari, Seyed-Saeed; Derakhshan, Somayeh (Frontiers in Public Health, 2023)
1 Abstract 1.1 Introduction: The IraPEN program is an adapted version of the WHO-PEN program designed to prevent four major non-communicable diseases in Iran. This study aims to determine the rate of compliance and related factors among individuals participating in the IraPEN program for the prevention of cardiovascular disease. 1.2 Method In this study, compliance was defined as timely referral to the health center as scheduled, and the researchers approached four pilot sites of IraPEN from March 2016 to March 2018. Sex-stratified logistic regressions were applied to investigate factors related to compliance. However, it is important to note that in this study, compliance was defined as compliance to revisit, not compliance to taking prescribed medications or behavioral lifestyle changes. 1.3 Results The total compliance rate, including timely compliance and early and late compliance, was 16.5% in men and 23.3% in women. The study found that cardiovascular risk factors such as diabetes, hypertension, hypercholesterolemia, and being underweight were associated with lower compliance. The higher calculated risk of CVD was associated with higher adherence, but after adjusting for cardiovascular risk factors, high-risk individuals showed lower adherence. There was negligible interaction between sex and other factors for compliance. 1.4 Conclusion The compliance rate with scheduled programs for cardiovascular preventive strategies was very low, and high-risk individuals were less compliant, regardless of their high level of risk factors. The study recommends further training to increase awareness and knowledge regarding the IraPEN program and the prevention of non-communicable diseases among high-risk populations.